EXPLORING STUDENTS’ PERCEPTIONS OF ICT-INTEGRATED PROJECT-BASED LEARNING IN AN EFL CRITICAL LISTENING COURSE - Soali, Muhammad; Hepriansyah, Azwan (J-LEE - Journal of Law, English, and Economics, 2025)
This study investigates the effectiveness of ICT-based Project-Based Learning (PjBL) in enhancing critical listening skills among fourth-semester students of the English Language Education program at Universitas Harapan Bangsa. In response to the growing demand for 21st-century skills and the integration of digital tools in language learning, the research applies a qualitative method through classroom-based observation, documentation, and interviews. Findings reveal that students not only showed improved comprehension and engagement in listening tasks but also developed higher-order thinking skills, collaboration, and digital literacy. ICT tools such as podcasts, video-based tasks, and interactive platforms were found to be instrumental in facilitating authentic and meaningful learning experiences. The use of PjBL also allowed students to take ownership of their learning, promoting autonomy and self-efficacy. Despite challenges such as varying digital proficiencies and time management issues, the results highlight the potential of ICT-integrated PjBL to transform traditional listening instruction into a more interactive, student-centered process. This study contributes to the body of knowledge on language pedagogy by offering empirical insights into how ICT and project-based methodologies can foster critical listening in higher education settings. Keywords: ICT integration, Project-Based Learning, critical listening, digital literacy, EFL learners, language pedagogy